Tennis champ. - Lunemann, Evelyn; Magnani, Rudolph (Westchester, Ill., Benefic Press, 1972)
Although she wants to please her father and win the tennis tournament, Mattie finds a sick child's needs more influential.
Keywords: Tennis stories